First report of Hemiberlesia cyanophylli (Signoret) (Hemiptera: Diaspididae) in Tunisia and North Africa - Ben Halima Kamel, Monia; Zouari, Sana; Ben Cheick, Zahra; KAYDAN BORA, Mehmet (ENTOMOLOGIA HELLENICA, 2025)
Hemiberlesia cyanophylli (Signoret, 1869) (Hemiptera: Coccomorpha: Diaspididae) was determined for the first time on Opuntia triacanthos Willd (Cactaceae) in a private garden at Akouda (Sousse, Tunisia) in 2022. The infestation was observed on the racket of O. triacanthos. This is the first record of H. cyanophylli in Tunisia, as well as for North Africa. Two other scale insects: Parlatoria oleae (Colvée, 1880) (Diaspididae) and Planococcus citri (Risso, 1813) (Hemiptera: Pseudococcidae) were also recorded on other ornamental plant species respectively, i.e. Rosa indica (Rosaceae) and Kalanchoë sp. (Crassulaceae).